Preparation method of modified nanocellulose, biomass coating and composite paper material
Modified nanocellulose and esterified modified starch were prepared by simulating the plant lignification process, forming biomass coatings that do not contain synthetic polymer materials with poor biodegradability, solving the problem of poor biodegradability in the coating and improving the physics of paper The strength and hydrophobicity achieve environmentally friendly modification effect.
Patent Information
- Application Number
- CN202411509790.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-13
AI Technical Summary
Existing white paper coated paints contain synthetic polymer materials with poor biodegradability, which makes it difficult for paper materials to degrade and cause environmental pollution.
The preparation method of modified nanocellulose is used to simulate the plant lignification process, and the reaction between DHP, cypress glucoside and carbohydrates is catalyzed by using the lignin oxidase system to form a firm chemical bond connection to prepare a biodegradable relationship without biodegradation. The biomass coating of polymer materials is synthesized and combined with esterified modified starch to form a hydrophobic coating.
The whiteness, strength and water resistance of paper are improved, while eliminating environmental pollution problems in traditional enhancement methods, providing environmentally friendly high physical strength and hydrophobic coatings.
Smart Images

Figure SMS_1 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomass paper materials, and in particular to a preparation method of modified nanocellulose, a biomass coating and a composite paper material. Background Art
[0002] In the field of paper packaging, in order to improve the performance of paper materials, the surface of paper materials is often modified to improve certain properties of paper materials. For example, coated white cardboard is often used in cigarette packaging. Coated white cardboard is a kind of cardboard that has been specially coated. It usually has high whiteness and smoothness, a smooth and delicate paper surface, and a good appearance and feel. In terms of printing, coated white cardboard can present clear, bright colors and fine patterns, which is very suitable for high-quality printing needs. The coating on its surface can also effectively prevent ink penetration, ensure the durability of the printing effect, and give the coated white cardboard a certain degree of water resistance and wear resistance.
[0003] The water resistance and wear resistance of coated white cardboard are usually given by coatings. In order to make the coating formed by the coating achieve the expected modification effect, the coating often contains some non-biomass additives. Although the coating has improved in environmental protection in recent years, there are still certain problems. For example, some coatings use solvents that may cause air pollution during the preparation and application process, and some coatings contain components with poor biodegradability. For example, the patent document with application number CN201811581120.X discloses a white cardboard, which includes a topcoat, a base paper layer and a primer layer arranged in sequence; the primer layer is formed by a coating; the coating includes carboxymethyl cellulose and / or polyvinyl alcohol, starch, esterified hemicellulose, acrylic acid-acrylonitrile copolymer, super absorbent resin and water. The coating of the above-mentioned white cardboard contains synthetic polymer materials with poor biodegradability such as acrylic acid-acrylonitrile copolymer and super absorbent resin, which makes the coating itself difficult to degrade, and the paper is easily discarded and causes long-term environmental pollution. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for preparing modified nanocellulose, wherein the modified cellulose can be used to prepare biomass coatings and form a coating on the surface of paper, which plays a role in improving the whiteness, strength and water resistance of the paper, and the formed coating does not contain synthetic polymer materials with poor biodegradability and is environmentally friendly.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing modified nanocellulose comprises the following steps: a. heating oxalic acid to a molten state, adding the bleached wood pulp to the molten oxalic acid, stirring and reacting at 100-150° C., then adding water to terminate the reaction, and separating and obtaining nanocellulose as a precipitate; b. dispersing nanocellulose in water to obtain a first suspension, mixing the first suspension, coniferyl alcohol solution, hydrogen peroxide solution and a first enzyme solution to obtain a first reaction solution, reacting at room temperature and separating to obtain DHP-nanocellulose as a precipitate; the first enzyme solution contains horseradish peroxidase; c. Dispersing DHP-nanocellulose in water to obtain a second suspension, mixing the second suspension with coniferyl glucoside, a second enzyme solution and a hydrogen peroxide solution, reacting at room temperature, and then separating to obtain modified nanocellulose as a precipitate; the second enzyme solution comprises β-glucosidase, glucose oxidase and horseradish peroxidase.
[0006] One of the important reasons why natural wood raw materials have good physical properties is that the plant fiber walls are connected by a lignin-rich composite intercellular layer CML, which contains about 60%-90% lignin and the rest is polysaccharides mainly composed of hemicellulose. The connection effect of CML includes the interpenetration effect between the three polymers of cellulose, hemicellulose and lignin, and the effect of lignin and carbohydrates forming LCC through covalent bonds. In particular, the LCC structure makes the connection between cellulose and hemicellulose in wood fibers and lignin very strong. After the wood raw materials are made into wood pulp, the interaction structure between polymers will be destroyed, so it is difficult for paper made from wood pulp to reproduce the good physical properties of wood. In this regard, the present invention simulates the plant lignification process, and adopts a lignin oxidase system to catalyze the free radical polymerization reaction between DHP, coniferyl alcohol glucoside and carbohydrates, so that crosslinking in the form of lignin-polysaccharide complexes such as anisole bonds and ester bonds and covalent bonds such as Beta-aryl ether bonds between lignins are regenerated between the separated fibers, so that strong chemical bond crosslinking is formed between the nanocelluloses, and finally the enzyme-catalyzed polymerization system is used to enhance the biodegradable "green" material based on the plant fiber, and some environmental pollution problems caused by the use of raw materials and products in the traditional enhancement method are fundamentally eliminated.
[0007] Furthermore, in step b, the first suspension, coniferyl alcohol solution and hydrogen peroxide solution are first mixed and homogenized by ultrasonication, and then the first enzyme solution is added to obtain a first reaction solution.
[0008] Furthermore, in step c, coniferyl glucoside is first dissolved in the second suspension, and then the second enzyme solution and the hydrogen peroxide solution are added in sequence to obtain a second reaction solution.
[0009] Furthermore, in step a, the mass ratio of oxalic acid to wood pulp is 1:(30~50).
[0010] Furthermore, in the first reaction solution, the mass ratio of coniferyl alcohol to nanocellulose is 1:(2-4).
[0011] Furthermore, in the first reaction solution, the mass ratio of horseradish peroxidase to hydrogen peroxide is 1:(50-180).
[0012] Furthermore, in the second reaction solution, the mass ratio of coniferyl glucoside to DHP-nanocellulose is 1:(2-5).
[0013] Furthermore, in the second reaction solution, the mass ratio of horseradish peroxidase to hydrogen peroxide is 1:(15-120), the mass ratio of β-glucosidase to coniferyl alcohol glucoside is 1:(5-40), and the mass ratio of glucose oxidase to coniferyl alcohol glucoside is 1:(5-40).
[0014] Furthermore, the solvent of the coniferyl alcohol solution is one or more of dichloromethane, ethyl acetate, toluene and n-hexane.
[0015] Another object of the present invention is to provide a biomass coating, which comprises esterified modified starch, water and the above-mentioned modified nanocellulose.
[0016] The biomass coating provided by the present invention does not contain volatile organic compounds and difficult-to-degrade synthetic polymer materials, and is good for the environment. The esterified modified starch serves as a thickener and adhesive for the coating on the one hand, and on the other hand, utilizes the esterified groups on its side chains to improve the hydrophobicity of the coating and enhance the waterproof effect.
[0017] Furthermore, the mass ratio of the modified nanocellulose to the esterified modified starch is (1~2):1.
[0018] Furthermore, the solid content of the coating is 3-5wt%.
[0019] Furthermore, the esterified modified starch is one or more of acetate starch or phosphate starch.
[0020] Another object of the present invention is to provide a composite paper material, comprising a substrate and a coating formed on the surface of the substrate, wherein the coating is formed by curing the above-mentioned biomass coating.
[0021] Furthermore, the substrate itself can be formed by a multi-layer structure. Taking one embodiment as an example, the substrate includes a surface layer, a core layer and a bottom layer, and the coating is applied on the surface of the surface layer.
[0022] The present invention further discloses a method for preparing a base layer in a further embodiment, wherein: the surface layer is made of 50-70% bleached conifer pulp and 30-50% bleached broadleaf pulp; the core layer is made of 10-20% bleached conifer pulp, 20-30% bleached broadleaf pulp, and 50-70% recycled pulp; the bottom layer is made of 30-50% bleached conifer pulp and 50-70% bleached broadleaf pulp. From the perspective of cost and material performance, conifer pulp has better printability but higher price, so its content is higher in the surface layer used for printing, while the appearance requirements of the core layer are lower, and a higher proportion of recycled pulp can be used to reduce costs.
[0023] In summary, the application of the present invention can achieve the following beneficial effects: 1. The present invention simulates the plant lignification process, so that the separated fibers can regenerate crosslinks in the form of lignin-polysaccharide complexes such as anisole bonds and ester bonds, as well as covalent bonds such as Beta-aryl ether bonds between lignins, thereby obtaining a modified nanofiber with high physical strength, which fundamentally eliminates some environmental pollution problems caused by the use of raw materials and products in traditional reinforcement methods.
[0024] 2. The biomass coating provided by the present invention has a simple composition, has high physical strength and good hydrophobicity after curing, does not require the addition of synthetic polymer materials and other modified substances, is highly safe and environmentally friendly.
[0025] 3. The composite paper material provided by the present invention has a coating on its surface, which can enhance the overall physical strength of the paper material and impart a certain hydrophobic property to the surface of the paper material, and is suitable for surface modification of coated white cardboard. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1 This embodiment provides a method for preparing modified nanocellulose, which is as follows: a. Heat oxalic acid at 100°C to a molten state, add bleached coniferous wood pulp to the molten oxalic acid at a ratio of oxalic acid to wood pulp solids = 1:30, and stir at 100°C for 20 minutes. After the reaction is completed, add 100 mL of 50°C water to terminate the reaction, then filter and wash to obtain nanocellulose as a precipitate; b. Disperse the nanocellulose in water, and ultrasonically homogenize it for 2 hours to obtain a first suspension containing 0.2 wt% of nanocellulose, take 10 g of the first suspension, dichloromethane (3 mL) containing 10 mg of coniferyl alcohol, and 300 μL of a 30% H2O2 solution, and ultrasonically homogenize to obtain a Pickering emulsion, and then add 100 μL of a 5.0 mg / mL horseradish peroxidase solution to the prepared Pickering emulsion to obtain a first reaction solution, and the first reaction solution is allowed to react at room temperature for 2 hours, and then the mixture is centrifuged at 12000 rpm for 10 minutes to collect DHP-nanocellulose as a precipitate; c. Dispersing the DHP-nanocellulose in water to obtain a second suspension containing 0.2wt% DHP-nanocellulose, preparing 1mL of a mixed enzyme solution with 5mg β-glucosidase, 5mg glucose oxidase and 5mg horseradish peroxidase, taking 20g of the second suspension, dissolving 20mg of coniferyl alcohol glucoside therein, adding 100μL of the mixed enzyme solution, and finally adding 200μL of a 30% mass concentration H2O2 solution to obtain a second reaction solution, stirring the second reaction solution at room temperature for 2h, and then centrifuging the mixture at 12000rpm for 10min, then washing with pure water, and finally drying to obtain modified nanocellulose.
[0028] Example 2 This embodiment provides a method for preparing modified nanocellulose, which is as follows: a. Heat oxalic acid at 120°C to a molten state, add bleached coniferous wood pulp to the molten oxalic acid at a ratio of oxalic acid to wood pulp solids = 1:40, and stir at 120°C for 30 minutes. After the reaction is completed, add 120 mL of 60°C water to terminate the reaction, then filter and wash to obtain nanocellulose as a precipitate; b. Disperse the nanocellulose in water, and ultrasonically homogenize it for 3 hours to obtain a first suspension containing 0.3 wt% of nanocellulose, take 30 g of the first suspension, dichloromethane (5 mL) containing 30 mg of coniferyl alcohol, and 400 μL of a 30% H2O2 solution, mix them, and ultrasonically homogenize them to obtain a Pickering emulsion, and then add 200 μL of a horseradish peroxidase solution with a concentration of 8.0 mg / mL to the prepared Pickering emulsion to obtain a first reaction solution, and the first reaction solution is allowed to react at room temperature for 3 hours, and then the mixture is centrifuged at 12000 rpm for 10 minutes to collect DHP-nanocellulose as a precipitate; c. Dispersing the DHP-nanocellulose in water to obtain a second suspension containing 0.3wt% DHP-nanocellulose, preparing 1mL of a mixed enzyme solution with 20mg β-glucosidase, 20mg glucose oxidase and 20mg horseradish peroxidase, taking 30g of the second suspension, dissolving 30mg of coniferyl alcohol glucoside therein, adding 200μL of the mixed enzyme solution, and finally adding 300μL of a 30% mass concentration of H2O2 solution to obtain a second reaction solution, stirring the second reaction solution at room temperature for 3h, and then centrifuging the mixture at 12000rpm for 10min, then washing with pure water, and finally drying to obtain modified nanocellulose.
[0029] Example 3 This embodiment provides a method for preparing modified nanocellulose, which is as follows: a. Heat oxalic acid at 150°C to a molten state, add bleached coniferous wood pulp to the molten oxalic acid at a ratio of oxalic acid to wood pulp solids = 1:50, and stir at 150°C for 50 minutes. After the reaction is completed, add 150 mL of 70°C water to terminate the reaction, then filter and wash to obtain nanocellulose as a precipitate; b. Disperse the nanocellulose in water, and ultrasonically homogenize it for 5 hours to obtain a first suspension containing 0.5 wt% of nanocellulose, take 40 g of the first suspension, dichloromethane (5 mL) containing 50 mg of coniferyl alcohol, and 500 μL of a 30% H2O2 solution, mix them, and ultrasonically homogenize them to obtain a Pickering emulsion, and then add 300 μL of a 10.0 mg / mL horseradish peroxidase solution to the prepared Pickering emulsion to obtain a first reaction solution, and the first reaction solution is allowed to react at room temperature for 5 hours, and then the mixture is centrifuged at 12000 rpm for 10 minutes to collect DHP-nanocellulose as a precipitate; c. Dispersing the DHP-nanocellulose in water to obtain a second suspension containing 0.5wt% DHP-nanocellulose, preparing 1mL of a mixed enzyme solution with 30mg β-glucosidase, 30mg glucose oxidase and 30mg horseradish peroxidase, taking 50g of the second suspension, dissolving 50mg of coniferyl alcohol glucoside therein, adding 300μL of the mixed enzyme solution, and finally adding 500μL of a 30% mass concentration of H2O2 solution to obtain a second reaction solution, stirring the second reaction solution at room temperature for reaction for 5h, and then centrifuging the mixture at 12000rpm for 10min, then washing with pure water, and finally drying to obtain modified nanocellulose.
[0030] Example 4 This embodiment provides a biomass coating and a composite paper material.
[0031] The biomass coating preparation method is as follows: The modified nanocellulose and acetate starch prepared in Example 1 were added to water in a ratio of 1:1 and mixed evenly to form a suspension, thereby preparing a biomass coating with a solid content of 3%.
[0032] The preparation method of the composite paper material is as follows: A substrate is prepared, wherein the substrate comprises a surface layer, a core layer and a bottom layer, wherein the surface layer is made of 50% bleached coniferous wood pulp and 50% bleached broadleaf wood pulp, the core layer is made of 10% bleached coniferous wood pulp, 20% bleached broadleaf wood pulp and 70% recycled pulp, and the bottom layer is made of 30% bleached coniferous wood pulp and 70% bleached broadleaf wood pulp, and the above-mentioned biomass coating is coated on the surface layer of the substrate, and after drying and curing, a composite paper material comprising a substrate and a coating is obtained.
[0033] Example 5 This embodiment provides a biomass coating and a composite paper material.
[0034] The biomass coating preparation method is as follows: The modified nanocellulose and acetate starch prepared in Example 2 were added to water in a ratio of 1.5:1 and mixed evenly to form a suspension, thereby preparing a biomass coating with a solid content of 4%.
[0035] The preparation method of the composite paper material is as follows: A substrate is prepared, wherein the substrate comprises a surface layer, a core layer and a bottom layer, wherein the surface layer is made of 60% bleached coniferous wood pulp and 40% bleached broadleaf wood pulp, the core layer is made of 15% bleached coniferous wood pulp, 25% bleached broadleaf wood pulp and 60% recycled pulp, and the bottom layer is made of 40% bleached coniferous wood pulp and 60% bleached broadleaf wood pulp, and the above-mentioned biomass coating is coated on the surface layer of the substrate, and after drying and curing, a composite paper material comprising a substrate and a coating is obtained.
[0036] Example 6 This embodiment provides a biomass coating and a composite paper material.
[0037] The biomass coating preparation method is as follows: The modified nanocellulose and acetate starch prepared in Example 3 were added to water in a ratio of 2:1 and mixed evenly to form a suspension, thereby preparing a biomass coating with a solid content of 5%.
[0038] The preparation method of the composite paper material is as follows: A substrate is prepared, wherein the substrate comprises a surface layer, a core layer and a bottom layer, wherein the surface layer is made of 70% bleached coniferous wood pulp and 30% bleached broadleaf wood pulp, the core layer is made of 20% bleached coniferous wood pulp, 30% bleached broadleaf wood pulp and 50% recycled pulp, and the bottom layer is made of 50% bleached coniferous wood pulp and 50% bleached broadleaf wood pulp, and the above-mentioned biomass coating is coated on the surface layer of the substrate, and after drying and curing, a composite paper material comprising a substrate and a coating is obtained.
[0039] Comparative Example 1 This comparative example provides a composite paper material, which comprises a surface layer, a core layer and a bottom layer, wherein the surface layer is made of 50% bleached coniferous pulp and 50% bleached broadleaf pulp, the core layer is made of 10% bleached coniferous pulp, 20% bleached broadleaf pulp and 70% recycled pulp, and the bottom layer is made of 30% bleached coniferous pulp and 70% bleached broadleaf pulp.
[0040] Comparative Example 2 This embodiment provides a composite paper material, and the preparation method thereof is as follows: a. Heat oxalic acid at 100°C to a molten state, add bleached coniferous wood pulp to the molten oxalic acid at a ratio of oxalic acid to wood pulp solids = 1:30, and stir at 100°C for 20 minutes. After the reaction is completed, add 100 mL of 50°C water to terminate the reaction, then filter and wash to obtain nanocellulose as a precipitate; b. Add nanocellulose and acetate starch into water in a ratio of 1:1 and mix well to form a suspension to prepare a biomass coating with a solid content of 3%; c. Prepare a substrate, the paper material comprising a surface layer, a core layer and a bottom layer, the surface layer is made of 50% bleached coniferous pulp and 50% bleached broadleaf pulp, the core layer is made of 10% bleached coniferous pulp, 20% bleached broadleaf pulp and 70% recycled pulp, and the bottom layer is made of 30% bleached coniferous pulp and 70% bleached broadleaf pulp; apply the above-mentioned biomass coating on the surface layer of the substrate, and obtain a composite paper material comprising the substrate and the coating after drying and curing.
[0041] Performance analysis: The composite paper materials prepared in Examples 4, 5, 6 and Comparative Examples 1 and 2 were subjected to the following tests.
[0042] ①Static bending strength analysis (three-point bending) The static bending strength of three-point bending is measured by applying a load to the middle of the specimen supported at two points. It is to determine the ratio of the bending moment and the bending section modulus of the specimen when the maximum load is applied. Cut a specimen of 15mm×200mm and place the specimen in an environment with a temperature of (20±2)℃ and a relative humidity of (65±5)% until the mass is constant. The mass is considered constant if the difference between the two weighing results 24 hours apart does not exceed 0.1% of the mass of the specimen. Adjust the span of the two supports to at least 20 times the basic thickness of the specimen, and measure the center distance of the supports to an accuracy of 0.5mm. The specimen is placed flat on the support, with the long axis of the specimen perpendicular to the support roller and the center point of the specimen below the loading roller.
[0043] Load at a constant rate throughout the test. Adjust the loading speed so that the maximum load is reached within (60 ± 30) s. Record the maximum load to the nearest 1% of the measured value.
[0044] The static bending strength of the sample is calculated according to the following formula, accurate to 0.1MPa: Where: ——static bending strength of the specimen, in megapascals (MPa); ——The maximum load when the specimen is damaged, in Newton (N); ——The distance between the two supports, in millimeters (mm); b ——Width of the specimen, in millimeters (mm); t ——Thickness of the specimen, in millimeters (mm).
[0045] ② Antibacterial experiment ① Prepare LB (beef extract peptone) solution Tryptone 10g / L; NaCl 10g / L; Yeast (yeast powder) 5g / L; pH = 7.0~7.4 ②Sample preparation The cigarette card paper prepared in the example was made into a circular sample with a diameter of 6 mm.
[0046] ③Sterilization operation Wrap the culture dish, spreader, deionized water (put in a conical flask), LB solution, and LB solution with 2% agar (20 g / L) (100 mL in each conical flask) in newspaper, place in an autoclave, and sterilize at 121°C for 45 minutes.
[0047] ④ Activation of E. coli Take 100 μL of the frozen Escherichia coli and put it in 5 mL of LB culture medium. Place the culture solution on a shaker at 37°C and 200 r / min. Take it out after 12 hours. Then take 100 μL of the above culture solution and put it in 5 mL of LB culture medium. Place the culture solution on a shaker at 37°C and 200 r / min. Take it out after 2 to 3 hours.
[0048] ⑤Measure OD value Take 1mL of the cultured bacterial solution, centrifuge at 8000r / min for 5min, pour off the supernatant and add 3mL of water, stir evenly and measure the absorbance of the bacterial solution in a UV spectrophotometer at 600nm, then dilute the bacterial solution (sterile water) to 5~5*106cfu / mL (1OD=1*109cfu / mL) ⑥ Experimental steps Place the above disinfected instruments and samples on a sterile workbench and irradiate with ultraviolet light for 30 minutes. Then pour the LB solution into the culture dish, about 30 mL each, and then let it stand for 15 minutes until the agar solidifies. Take 200 μL of the diluted bacterial solution in the culture dish, rotate the culture dish to evenly distribute the bacterial solution on the surface, let it stand for about 15 minutes, and stick the sample on the surface of the culture medium, with 3 pieces of cigarette card paper samples in the example attached to each dish. Cover the culture dish with a lid, seal it with a sealing film, and put it in an incubator at 37.5°C. After 7 hours, observe and measure the diameter of the antibacterial zone around the sample and keep a record.
[0049] ③Contact angle test (surface properties) The contact angle refers to the angle θ between the tangent line of the gas-liquid interface at the intersection of the gas, liquid and solid phases and the solid-liquid boundary line on the liquid side, which is a measure of the degree of wettability. The contact angle is measured under standard atmospheric pressure (101.3 kPa) and room temperature (25°C), as follows: (1) Cut a number of samples of varying sizes (they can be placed flat on the stage of the contact angle meter) and put them into numbered sample bags with a certain amount of distilled water.
[0050] (2) Turn on the contact angle meter, use the injection needle to absorb a certain amount of water, and load it into the syringe loading area of the meter. Then place the paper sample to be tested on the stage and adjust the light intensity until the display is clear.
[0051] (3) Use software to control the syringe to drip liquid onto the paper surface. When dripping distilled water, choose manual addition. The dripping of one drop of water is considered as the standard. Take a screenshot of the moment when the drop contacts the sample surface and save it. Use the image analysis method in the software to fit the contact angle in the picture and record the contact angle.
[0052] The test results are shown in the following table.
[0053] It can be seen from the above table that compared with Comparative Example 1, the three composite paper materials prepared in Examples 4 to 6 all have a certain antibacterial effect and good hydrophobicity. As the coating ratio in Examples 4 to 6 changes, the antibacterial effect and hydrophobicity change. When the solid content in the coating is increased and the proportion of modified nanocellulose is increased, the antibacterial effect and hydrophobicity of the composite paper are further improved. In addition, the bending strength of the paper will also be significantly improved. The nanocellulose in the coating of the composite paper prepared in Comparative Example 2 is not cross-linked, and its bending strength and hydrophobicity are lower than those in Example 4, and the antibacterial performance is lost. It can be seen that the cross-linked nanocellulose has obvious improvements in physical and chemical properties.
[0054] In summary, the modified nanocellulose provided by the present invention can increase the physical strength of paper when applied to paper coating, and can also give the paper certain antibacterial and hydrophobic properties, and is suitable for special packaging materials.
[0055] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing modified nanocellulose, comprising the following steps: a. heating oxalic acid to a molten state, adding the bleached wood pulp to the molten oxalic acid, stirring and reacting at 100-150° C., then adding water to terminate the reaction, and separating and obtaining nanocellulose as a precipitate; b. dispersing nanocellulose in water to obtain a first suspension, mixing the first suspension, coniferyl alcohol solution, hydrogen peroxide solution and a first enzyme solution to obtain a first reaction solution, reacting at room temperature and separating to obtain DHP-nanocellulose as a precipitate; the first enzyme solution contains horseradish peroxidase; c. Dispersing DHP-nanocellulose in water to obtain a second suspension, mixing the second suspension with coniferyl glucoside, a second enzyme solution and a hydrogen peroxide solution, reacting at room temperature, and then separating to obtain modified nanocellulose as a precipitate; the second enzyme solution comprises β-glucosidase, glucose oxidase and horseradish peroxidase.
2. The method for preparing modified nanocellulose according to claim 1, characterized in that: In step b, the first suspension, coniferyl alcohol solution and hydrogen peroxide solution are first mixed and homogenized by ultrasonication, and then the first enzyme solution is added to obtain a first reaction solution.
3. The method for preparing modified nanocellulose according to claim 1, characterized in that: In step c, coniferyl glucoside is first dissolved in the second suspension, and then the second enzyme solution and the hydrogen peroxide solution are added in sequence to obtain a second reaction solution.
4. The method for preparing modified nanocellulose according to claim 1, characterized in that: In step a, the mass ratio of oxalic acid to wood pulp is 1:(30-50).
5. The method for preparing modified nanocellulose according to claim 1, characterized in that: In the first reaction solution, the mass ratio of coniferyl alcohol to nanocellulose is 1:(2-4).
6. The method for preparing modified nanocellulose according to claim 1, characterized in that: In the first reaction solution, the mass ratio of horseradish peroxidase to hydrogen peroxide is 1:(50-180).
7. The method for preparing modified nanocellulose according to claim 1, characterized in that: In the second reaction solution, the mass ratio of coniferyl glucoside to DHP-nanocellulose is 1:(2-5).
8. The method for preparing modified nanocellulose according to claim 1, characterized in that: In the second reaction solution, the mass ratio of horseradish peroxidase to hydrogen peroxide is 1:(15-120), the mass ratio of β-glucosidase to coniferyl alcohol glucoside is 1:(5-40), and the mass ratio of glucose oxidase to coniferyl alcohol glucoside is 1:(5-40).
9. A biomass coating, characterized in that: The invention comprises esterified modified starch, water and the modified nanocellulose according to any one of claims 1 to 8.
10. A composite paper material, characterized in that: The invention comprises a substrate and a coating formed on the surface of the substrate, wherein the coating is formed by curing the biomass coating according to claim 9.
Citation Information
Patent Citations
Method for enhancing paper strength based on enzymatic catalytic lignin dehydrogenized polymer
CN106522013A
Method for preparing nanocellulose whiskers and fibrils by means of acidolysis of oxalic acid
CN108457112A
Manufacture of nanocellulose and intermediates thereof using oxalic acid dihydrate
CN108779183A
Manufacture of hydrophobized nanocellulose intermediate as well as hydrophobized nanocellulose
CN110914356A
Manufacture of nanocellulose and intermediates thereof
US20180291119A1
Cited By
Biomass coating for paper-based packaging material and preparation method of biomass coating
CN121250709A
Waterproof and moistureproof degradable paper as well as preparation method and application thereof
CN121931743A
Waterproof and moisture-proof degradable paper and preparation method and application thereof
CN121931743B
